Development of an algorithm which generates functional floor plans for residential buildings based on modular construction - Costa, João Francisco Rodrigues (2015)
Dissertação de Mestrado Integrado em Engenharia Civil apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra